6TiSCH minimal scheduling function: Performance evaluation. Issue 4 (11th June 2020) - Chang, Tengfei; Vučinić, Mališa; Guillén, Xavier V.; Dujovne, Diego; Watteyne, Thomas
Abstract : 6TiSCH is a standardization group within the Internet Engineering Task Force (IETF) that works on IPv6‐enabled Time‐slotted Channel Hopping (TSCH) networks. The 6TiSCH protocol stack, designed by the standardization work at the IETF, has direct applicability to low‐power Internet of Things (IoT) use cases, including smart factory, building, infrastructure and home applications. A key component of the 6TiSCH stack is the Minimal Scheduling Function (MSF). MSF implements a traffic adaptation algorithm which allocates link‐layer resources, that is, cells in the TSCH schedule, according to the traffic load. MAX_NUMCELL is an important parameter defined in the MSF draft standard which determines the length of the running window used to measure cell usage. MSF draft standard does not recommend a value of MAX_NUMCELL to use. This paper provides recommendations on how to choose the value of MAX_NUMCELL, validated through simulation. For periodic traffic, setting MAX_NUMCELL to at least four times the traffic load is recommended to increase efficiency. For bursty traffic, we show that setting MAX_NUMCELL to a small value achieves a low end‐to‐end latency but at high communication overhead. In addition, an improved version of MSF is implemented and tested, which shows a 44% reduction in the communication overhead, considering MAX_NUMCELL = 4, while maintaining the same end‐to‐end latency.